Perioperative nutrition : ERAS special group discussion - Luciana B Sutanto; Nurul Ratna Mutu Manikam; Adianto Nugroho (Indonesian Nutrition Association, 2023)
Nutrition is one of the vital role in improving the healing and recovery after surgery, either preoperative (before surgery), intraoperative (during surgery), or postoperative (after surgery). The Enhanced Recovery After Surgery (ERAS) Society has published a multidisciplinary approach to perioperative care aimed at achieved early recovery for patients undergoing major surgery.